The Allocation of Capital and Time over the Business Cycle - Greenwood, Jeremy; Hercowitz, Zvi (Journal of Political Economy, 1991)
A Beckerian model of household production is developed to study the cyclical allocation of capital and time between market and home activities. The adopted framework treats the business and household sectors symmetrically. In the market, labor interacts with business capital to produce market goods and services, and likewise at home the remaining time (leisure) is combined with household capital to produce home goods and services. The model presented is parameterized and simulated to see whether it can rationalize the observed allocation of capital and time, as well as other stylized facts, for the postwar U.S. economy.